Molecular diversity and relationships of fig associated nematodes from South Africa. - Meike S Kruger (Public Library of Science (PLoS), 2021)
Nematodes of figs and fig wasps have received limited attention in Africa since their discovery in 1973. Sixteen of the 25 species of native South African figs were sampled for nematode associates using molecular barcoding with three loci (SSU, LSU D2-D3 and mtCOI) and fourteen (93%) were positive for at least one nematode species. Thirty-three putative species of nematodes were identified and classified according to the loci that were amplified and successfully sequenced. Fourteen putative nematode species were classified as Aphelenchoididae, of which nine were identified as Ficophagus from four species of Ficus from the section Galoglychia (i.e., five ex F. burkei including one shared with F. natalensis, one ex F. glumosa, one ex F. lutea, and one ex F. stuhlmannii) and one species ex F. sur from the section Sycomorus. In addition, there were four nematode species classified as Schistonchus s.s. from section Galoglychia figs (i.e., one ex F. burkei, two ex F. trichopoda, and one ex F. glumosa). There was also one species of Bursaphelenchus nematode recovered from F. sur from the section Sycomorus. Sixteen putative nematode species were classified as Diplogastridae, of which eight occurred in two clades of what is currently called Parasitodiplogaster with one (P. salicifoliae) being recovered from two Ficus species in the section Urostigma (F. salicifolia and F. ingens) and seven diplogastrids being associated with six species of Ficus from the section Galoglychia (i.e., two ex F. burkei including P. sycophilon, one ex F. stuhlmannii, one ex F. burtt-davyi, one ex F. trichopoda, one ex F. abutilifolia and one ex F. sansibarica). Three Acrostichus spp., a Teratodiplogaster and a Pristionchus species were recovered from F. sur and two Teratodiplogaster spp. and Pristionchus sycomori were recovered from F. sycomorus with both Ficus species belonging to the subgenus and section Sycomorus. The identities of the previously described T. martini and Parasitodiplogaster doliostoma (= Pristionchus sp. 35) are discussed. Lastly, there was a panagrolaimid identified from F. petersii.